VR/MR Supporting the Future of Defensive Cyber Operations. Issue 19 (2019) - Kullman, Kaur; Ryan, Matt; Trossbach, Lee
Abstract: US Army C5ISR Center Cyber Security Service Provider (CSSP) is a 24/7 Defensive Cyber Operations (DCO) organization that defends US Department of Defense and US Army networks from hostile cyber activity, as well as develops technologies and capabilities for use by DCO operators within the DoD. In recent years, C5ISR Center CSSP has been researching various advanced data visualization concepts and strategies to enhance the speed and efficiency of cybersecurity analyst's workflow. To achieve these goals Virtual and Mixed Reality (VR/MR) tools have been employed to investigate, whether these mediums would enable useful remote collaboration of DCO operators and whether stereoscopically perceivable 3D data visualizations would enable DCO operators to gain improved hindsight into their datasets. We'll be giving overview of the capabilities being developed as aligned to our research and operational requirements, our expected outcomes of using VR/MR in training and operational cyber environments and our planned path to accomplish these goals.